Children’s eating behaviour: A comparison between normal, overweight and obese children - Lily Shuzeen Kimin; Constance Liew Sat Lin; Richard Avoi; Firdaus Hayati; Mohd Nazri Mohd Daud; Symeon Mandrinos; Alvin Oliver Payus (Elsevier B.V., 2022)
Background: Childhood obesity has become a major global health concern and has been increasing dramatically over the years. Previous study has shown that specific eating behaviours may have been associated with obesity especially under-responsiveness to internal satiety cues and over-responsiveness to external food cues such as the taste, smell, availability and emotions. However, there is still inadequate number of studies present to describe the association between the children’s body mass index (BMI) and their eating behaviours, especially in Sabah, Malaysia. Therefore, the objective of this study is to established the association between the children’s eating behaviours with their nutritional status based on their body mass index. Materials and methods: A cross-sectional study involving 484 children aged 6–12 years old was conducted in Kota Kinabalu, which is a developing urban area in Sabah. The children were recruited from five primary schools that were selected based on multistage stratified and convenience sampling method. Sociodemographic details and anthropometric measures both parents and children, and eating behaviours of children were assessed using Children Eating Behaviour Questionnaires (CEBQ). Age-adjusted BMI z-scores were then calculated according to the World Health Organization recommendations to assess nutritional status. Results: The prevalence of childhood obesity among children aged 6–12 years old is 13.2%. The mean scores of ‘Food Approach’ subscales from the CEBQ showed higher mean score in overweight and obese groups as compared to the mean score in normal weight group. The mean scores of ‘Food Avoidance’ subscales showed lower mean score in overweight and obese groups as compared to mean score in normal weight group. Conclusion: This study provides evidence that childhood obesity is yet to be a prevalent health problem in a developing urban area considering the “Food approach” subscales were positively associated with the excess weight in children.